Modernization of the Speed Regulator: Benefits for Efficiency and Stability in Electrical Generation - Electroperú S.A. - Payano Hinostroza, Franco Julinho (2025)
The research aimed to present an analysis of the technical, operational, and economic benefits obtained by modernizing the speed regulator of a hydroelectric power plant in Peru. The results show that the modernization significantly improved the dynamic response to frequency disturbances, eliminated penalties for regulatory non-compliance, obtained economic incentives for better primary regulation performance, and achieved more efficient turbine operation. In addition, the economic savings and additional income generated by these benefits were quantified, demonstrating that the investment made was an adequate and profitable solution for this type of hydroelectric power plants. Finally, recommendations are made for regulatory agencies and the electricity system operator to promote the modernization of frequency regulation systems in other generating plants, considering the benefits this generates for the stability and reliability of the electrical system.